All-solid-state battery and preparation method of all-solid-state battery
By adjusting the actual expansion ratio of the positive electrode layer and the negative electrode layer in the all-solid battery, the difference is below 10%, the problem of increasing interface resistance during charging and discharging is solved, and the stability of cycling performance and the long life of the battery are achieved.
Patent Information
- Application Number
- CN202380051322.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-12
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-28
AI Technical Summary
During the charging and discharging process of all-solid batteries, the interface contact area between the solid electrolyte layer and the electrode layer is reduced due to the expansion and contraction of the active substance, resulting in an increase in interface resistance and a significant decrease in cycling performance.
By adjusting the actual expansion ratio of the positive electrode layer and the negative electrode layer, the difference is below 10%, ensuring that the expansion and contraction changes of the positive electrode layer and the negative electrode layer are close during the charging and discharging process, thereby suppressing the compression and release of the solid electrolyte layer and maintaining the stability of the interface contact area.
The cycle performance reduction caused by the increase of interface resistance is effectively suppressed, and the cycle characteristics of the battery can be maintained even when the battery is repeatedly charged and discharged.
Smart Images

Figure CN119547237A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an all-solid-state battery having a solid electrolyte layer and a method for preparing the same, and in particular to an all-solid-state battery and a method for preparing the same, which can suppress the increase in resistance caused by repeated charging and discharging at the interface between the solid electrolyte layer and the electrode layer. Background Art
[0002] As a power source installed on a vehicle driven by electricity, etc., or installed on an electrical product such as a personal computer and a portable terminal, a secondary battery with a higher output and a higher capacity can be achieved by using a lithium-ion secondary battery, etc. Among these secondary batteries, in particular, a lithium-ion secondary battery is light in weight and has a high energy density, and is preferably used as a high-output power source for vehicles such as electric vehicles (EVs), plug-in hybrid vehicles (PHVs), and hybrid vehicles (HVs), and it is expected that demand will increase in the future.
[0003] In addition, in recent years, as a form of secondary battery, a battery in which a solid electrolyte in powdered, granular, or plate-shaped form is used instead of a liquid electrolyte (electrolyte), also known as an all-solid-state battery, has been subject to various research and development efforts for its practical application.
[0004] Since all-solid-state batteries do not use liquid electrolytes (especially non-aqueous electrolytes), it is possible to easily construct a stacked electrode body having a stacked structure consisting of a positive electrode layer, a negative electrode layer, and a solid electrolyte layer without the complicated processing required when handling organic solvents such as non-aqueous electrolytes.
[0005] In addition, since no electrolyte is used, the structure of the electrode body becomes simple, which also helps to improve the battery capacity per unit volume of the battery. Moreover, since no electrolyte is used, it is safe. Therefore, it is expected to be used as a high-output power source for driving vehicles requiring higher capacity.
[0006] Furthermore, as a measure for increasing the capacity, for example, Patent Document 1 discloses a negative electrode and a negative electrode material (negative electrode active material) for all-solid-state batteries that are preferred for achieving high energy density and capacity retention rate.
[0007] Prior art documents
[0008] Patent Documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2017-054720 Summary of the invention
[0010] Problems to be solved by the present invention
[0011] However, as one of the topics of all-solid batteries, it is known that due to the expansion and contraction of the active material during charge and discharge, gaps and cracks may be generated at the interface of the solid electrolyte layer and the positive electrode layer and / or the negative electrode layer. In particular, as described in patent document 1, the active material with high energy density changes in volume due to the conversion reaction during charge and discharge, and the ratio of its expansion and contraction is large. Therefore, if charge and discharge are repeated, the interface contact between the positive electrode layer or the negative electrode layer and the solid electrolyte layer is reduced, and the interface resistance increases. When such an increase in interface resistance is generated, the cycle characteristics of the all-solid battery are significantly reduced each time it is charged and discharged.
[0012] The present invention is created to solve such problems related to all-solid-state batteries, and its purpose is to provide an all-solid-state battery that prevents the reduction in contact area between the solid electrolyte layer and the electrode due to expansion of the active material during charging and discharging, thereby inhibiting the reduction in cycle performance due to an increase in interface resistance.
[0013] Means of solving the problem
[0014] According to this embodiment, an all-solid-state battery is provided, which has a stacked structure of a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and a solid electrolyte layer containing a solid electrolyte, and has suppressed reduction in cycle performance.
[0015] That is, the all-solid-state battery of the present embodiment is an all-solid-state battery that is charged and discharged through a conversion reaction, and has a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and a solid electrolyte layer containing a solid electrolyte formed between the positive electrode layer and the negative electrode layer, wherein the absolute value of the difference [(Ep)-(En)] between the actual expansion ratio (Ep) of the positive electrode layer calculated by the following formula (1) and the actual expansion ratio (En) of the negative electrode layer calculated by the following formula (2) is less than 10%.
[0016] Actual expansion ratio of positive electrode layer (Ep) = expansion ratio of positive electrode layer × thickness ratio of positive electrode layer (1) Actual expansion ratio of negative electrode layer (En) = expansion ratio of negative electrode layer × thickness ratio of negative electrode layer (2)
[0017] The preparation method of the all-solid-state battery in the present embodiment is a method for preparing an all-solid-state battery that is charged and discharged by a conversion reaction, the method comprising: a process of preparing a positive electrode layer comprising a positive electrode active material, a negative electrode layer comprising a negative electrode active material, and a solid electrolyte layer comprising a solid electrolyte; and a process of stacking the positive electrode layer, the negative electrode layer, and the solid electrolyte layer in a manner arranged between the positive electrode layer and the negative electrode layer, and applying pressure in the stacking direction, wherein the absolute value of the difference between the actual expansion ratio (Ep) of the positive electrode layer calculated by the following formula (1) and the actual expansion ratio (En) of the negative electrode layer calculated by the following formula (1) is less than 10%.
[0018] Actual expansion ratio of positive electrode layer (Ep) = expansion ratio of positive electrode layer × thickness ratio of positive electrode layer (1) Actual expansion ratio of negative electrode layer (En) = expansion ratio of negative electrode layer × thickness ratio of negative electrode layer (2)
[0019] Effects of the Invention
[0020] According to the all-solid-state battery and the method for producing the all-solid-state battery disclosed in the present application, it is possible to provide an all-solid-state battery in which a decrease in cycle performance due to an increase in interface resistance is suppressed even when charge and discharge are repeated. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a cross-sectional view showing a schematic structure of the all-solid-state battery according to the present embodiment.
[0022] Figure 2A It is used to illustrate Figure 1 Schematic diagram of the charging and discharging behavior of an all-solid-state battery after initial charging.
[0023] Figure 2B It is used to illustrate Figure 1 Schematic diagram of the behavior of an all-solid-state battery during charge and discharge after an initial discharge.
[0024] Figure 3 This is a schematic diagram for explaining the behavior of a conventional all-solid-state battery during charge and discharge. DETAILED DESCRIPTION
[0025] <Preliminary research items>
[0026] First, the inventors studied the degradation of the cycle characteristics during charge and discharge when using materials with large expansion coefficients in all-solid batteries. In the study, negative electrode active materials with relatively large expansion and contraction during charge and discharge were used as negative electrode active materials, and positive electrode active materials with relatively small expansion and contraction during charge and discharge were used as positive electrode active materials, and their cycle characteristics were studied.
[0027] In this previous study, regarding the principle of the reduction in cycle characteristics, a schematic diagram for explaining the behavior during charge and discharge is shown below. Figure 3 As shown below, refer to Figure 3 Provide explanation.
[0028] First, a fully solid battery 50 is prepared, which is stacked with a positive electrode layer 51, a negative electrode layer 52, a solid electrolyte layer 53 formed between the positive electrode layer 51 and the negative electrode layer 52, and also has a positive electrode collector 54 and a negative electrode collector 55 ( Figure 3 (a) Here, the negative electrode layer 52 contains Si (silicon) as a negative electrode active material, and the positive electrode layer 51 contains LiCoO 2 as a positive electrode active material.
[0029] Next, the all-solid battery 50 is initially charged or initially discharged. The following is an example of initial charging. In the initial charging, the negative electrode layer 52 expands greatly in the stacking direction because the silicon contained in it has an expansion rate of more than 10%, while the positive electrode layer 51 does not expand in the stacking direction because it is a material that hardly expands, and the solid electrolyte layer 53 is compressed ( Figure 3 (b)). In addition, here, the expansion is represented by a solid arrow, and the contraction is represented by a dotted arrow. The same applies to the following description. Figure 2A and Figure 2B .
[0030] When discharging is performed after charging is completed, the negative electrode layer 52 contracts, and the compressed solid electrolyte layer 53 ( Figure 3 (c) At this time, since a force acts in the direction of separation between the negative electrode layer 52 and the solid electrolyte layer 53, a gap or crack is generated at their interface, and the contact area is likely to decrease.
[0031] Furthermore, when charging and discharging are repeated after the discharge operation, Figure 3 (b) and Figure 3 The state change of (c) is repeated, and the compression and release of the solid electrolyte layer 53 are repeated due to the expansion and contraction of the negative electrode layer 52. Therefore, it can be considered that the interface resistance is likely to increase, the battery capacity is reduced, and the cycle characteristics of the all-solid battery are significantly deteriorated.
[0032] In fact, when evaluating the cycle characteristics of an all-solid-state battery composed of a positive electrode layer containing the above-mentioned positive electrode active material and a negative electrode layer containing the above-mentioned negative electrode active material, it was confirmed that the capacity retention rate decreased to about 30% relative to the first cycle when 50 charge and discharge cycles were performed.
[0033] In the above-mentioned research items, the case of starting from the initial charge is described, but it is assumed that even in the case of the initial discharge, the same phenomenon will occur due to repeated charge and discharge, and the cycle characteristics are still likely to deteriorate.
[0034] <Implementation Method>
[0035] Hereinafter, the embodiments will be described in detail based on the examples and drawings. In all drawings for describing the embodiments, components having the same functions are represented by the same or related symbols, and their repeated descriptions are omitted.
[0036] [All-solid-state battery]
[0037] As an all-solid-state battery of one embodiment of the present invention, for example, Figure 1 As shown, an all-solid battery 10 including a positive electrode layer 11 , a negative electrode layer 12 , a solid electrolyte layer 13 formed between the positive electrode layer 11 and the negative electrode layer 12 , a positive electrode collector 14 , and a negative electrode collector 15 can be exemplified.
[0038] In addition, in the following description, as the applicable object of the technology disclosed herein, an all-solid lithium ion secondary battery is taken as an example, but it is not limited thereto. As the type of all-solid battery disclosed herein, it can be an all-solid battery using other metal ions as charge carriers, for example, an all-solid battery composed of a sodium ion secondary battery, a magnesium ion secondary battery, etc.
[0039] Here, the all-solid-state battery 10 is a battery that is charged and discharged by a conversion reaction. In the conversion reaction, for example, unlike the intercalation reaction in which lithium ions enter and exit the interlayer of the active material, a redox reaction is performed between the active material and the lithium ions, thereby performing charging and discharging. At this time, the active material expands or contracts due to the conversion reaction, so its volume change is large.
[0040] In this embodiment, the positive electrode active material and / or the negative electrode active material can be any active material that performs a conversion reaction. That is, at least one of the positive electrode active material and the negative electrode active material can be any active material that performs a conversion reaction. According to this embodiment, even in the case of having an active material that performs such a conversion reaction, an all-solid battery can be made that can fully suppress the reduction in cycle performance caused by its expansion or contraction.
[0041] (Positive electrode layer)
[0042] The positive electrode layer 11 used in this embodiment is a positive electrode layer containing a positive electrode active material. Here, the positive electrode active material refers to a substance that participates in the absorption and release of charge carriers (for example, lithium ions in a lithium ion secondary battery) on the positive electrode side.
[0043] As the positive electrode active material, conventionally known positive electrode active materials can be used, for example, preferably active materials of conversion types such as CuCl2, FeF2, S, AgCl, FeCl3, NiCl2, CoCl2, FeCl2, Li2S, LiCl, LiF, AgF, Br2, LiBr, CoF3, CuF2, CuF, BiF3, CuCl2, NiF2, LiI, I2, CoF2, FeF3, MnF3, CrF3, CuS, Li2Se, Se, CuSe, Cu2O, CoS2, Cu2S, NiS, FeS2, Te, Li2Te, VF3, FeS, CoSe2, MnS2, MnCl2, Co3S4, FeSe, TiF3, and MnS. Among them, CuCl2, FeF2, and S are preferred.
[0044] The positive electrode active material used here is contained in the form of particles, and the average particle size (D50) thereof based on a laser diffraction scattering method is, for example, preferably about 0.5 μm to 20 μm, and more preferably about 1 μm to 10 μm.
[0045] In addition, the positive electrode layer 11 may contain a solid electrolyte in addition to the positive electrode active material. Furthermore, various optional components may be contained in the same manner as the positive electrode layer of such a conventional battery. Examples of the optional components include a conductive auxiliary agent and a binder.
[0046] As the solid electrolyte that can be used here, various oxide-based solid electrolytes or sulfide-based solid electrolytes can be cited. As the oxide-based solid electrolyte, various oxides having a NASICON structure, a garnet structure, or a perovskite structure can be cited as a preferred substance.
[0047] For example, the general formula: Li x AO y (herein, A is B, C, Al, Si, P, S, Ti, Zr, Nb, Mo, Ta or W; x and y are positive real numbers). Specific examples include Li3BO3, LiBO2, Li2CO3, LiAlO2, Li4SiO4, Li2SiO3, Li3PO4, Li2SO4, Li2TiO3, Li4Ti5O 12 , Li2Ti2O5, Li2ZrO3, LiNbO3, Li2MoO4, Li2WO4, etc. Alternatively, preferred materials include glasses or glass ceramics such as Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3, and Li2O-B2O3-ZnO.
[0048] In particular, from the viewpoint of having high ion conductivity, it is preferred to use a sulfide-based solid electrolyte, for example, glasses or glass ceramics such as Li2S-SiS2, Li2S-P2S3, Li2S-P2S5, Li2S-GeS2, Li2S-B2S3, Li3PO4-P2S5, and Li4SiO4-Li2S-SiS2 can be cited.
[0049] In addition, from the viewpoint of achieving higher ion conductivity, it is preferred to use a solid solution based on Li2S composed of Li2S and lithium halide (e.g., LiCl, LiBr, LiI). Preferred substances include LiBr-Li2S-P2S5, LiI-Li2S-P2S5, LiBr-LiI-Li2S-P2S5, etc.
[0050] The solid electrolyte used is in a particle form, and its average particle size (D50) based on a laser diffraction scattering method is, for example, preferably 0.1 μm to 10 μm, and more preferably 0.4 μm to 5 μm.
[0051] As the conductive aid that can be used here, as a preferred conductive aid, carbon black such as acetylene black or other carbon materials (graphite, carbon nanotubes, etc.) can be mentioned.
[0052] As the binder that can be used here, as preferred binders, there are fluorine-based binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), and rubber-based binders such as styrene butadiene rubber (SBR).
[0053] When the positive electrode layer 11 is formed by containing a positive electrode active material, a solid electrolyte, a conductive aid and a binder, when the content ratio of the positive electrode active material: conductive aid: binder: solid electrolyte = x: y: z: v is expressed by the mass basis, it is preferred that the content ratio (mass %) is in the range of 50≤x≤92.5, 2.5≤y≤45, 2.5≤z≤45, 2.5≤v≤45. Furthermore, these ratios are more preferably in the range of 65≤x≤92.5, 2.5≤y≤20, 2.5≤z≤15, 2.5≤v≤20.
[0054] The thickness of the positive electrode layer 11 is not particularly limited as long as the relationship described later is satisfied. For example, the thickness of the positive electrode layer 11 is preferably in the range of 10 μm to 500 μm.
[0055] (Negative electrode layer)
[0056] The negative electrode layer 12 used in this embodiment is a negative electrode layer containing a negative electrode active material. Here, the negative electrode active material refers to a substance that participates in the absorption and release of charge carriers (for example, lithium ions in a lithium ion secondary battery) on the negative electrode side.
[0057] Examples of the negative electrode active material include conversion-type active materials such as Si-based, Li-based, Sn-based, Mg-based, and Al-based materials. Among them, Si-based, Li-based, Mg-based, and Al-based active materials are preferred from the perspective of high energy density per unit weight or unit volume.
[0058] Examples of Si-based negative electrode active materials include Si, SiO a (here 0.05<a<1.95) represented by silicon oxide, SiC b Silicon carbide represented by (0<b<1), SiN c Silicon nitride represented by (0<c<4 / 3) or the like.
[0059] In addition, as other examples of silicon-based negative electrode active materials, alloy materials composed of silicon and elements other than silicon can be cited. As elements other than silicon, for example, C, Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, etc. can be cited.
[0060] Examples of Sn-based negative electrode active materials include tin, tin oxides, tin nitrides, tin-containing alloys, and solid solutions thereof. Some of the tin atoms contained in these materials may be substituted with one or more elements.
[0061] As oxides, SnO d Tin oxide, tin dioxide (SnO2), etc. represented by (0<d<2). Examples of tin-containing alloys include Ni-Sn alloys, Mg-Sn alloys, Fe-Sn alloys, Cu-Sn alloys, Ti-Sn alloys, etc. Examples of tin compounds include SnSiO3, Ni2Sn4, Mg2Sn, etc.
[0062] Examples of the Li-based negative electrode active material include Li, In-Li alloy, Al-Li alloy, Mg-Li alloy, Zn-Li alloy, Sn-Li alloy, and Sb-Li alloy.
[0063] Examples of the Mg-based negative electrode active material include Mg, Ni-Mg alloy, Sn-Mg alloy, Fe-Mg alloy, Cu-Mg alloy, and Ti-Mg alloy.
[0064] Examples of the Al-based negative electrode active material include Al, Ni—Al alloy, Sn—Al alloy, Fe—Al alloy, Cu—Al alloy, and Ti—Al alloy.
[0065] The negative electrode active material used here is contained in the form of particles, and the average particle size (D50) thereof based on a laser diffraction scattering method is, for example, appropriately about 1 μm to 20 μm, and particularly preferably about 2 μm to 10 μm.
[0066] In addition, the negative electrode layer 12 may contain a solid electrolyte in addition to the negative electrode active material. Furthermore, various optional components may be contained in the same manner as the negative electrode layer of such a conventional battery. Examples of the optional components include a conductive auxiliary agent, a binder, and the like.
[0067] The solid electrolyte, conductive additive, and binder contained in the negative electrode layer 12 may be the same as the above-mentioned arbitrary components contained in the positive electrode layer 11. Therefore, detailed description of these components is omitted.
[0068] The thickness of the negative electrode layer 12 is not particularly limited as long as the relationship described below is satisfied. For example, the thickness of the negative electrode layer 12 is preferably in the range of 10 μm to 500 μm.
[0069] (Solid electrolyte layer)
[0070] The solid electrolyte layer 13 used in the present embodiment may be composed of a known solid electrolyte layer used in all-solid batteries, and may contain various solid electrolytes as in the related art without any limitation.
[0071] like Figure 1 As shown, the solid electrolyte layer 13 is formed between the positive electrode layer 11 and the negative electrode layer 12, and is configured so that charge carriers such as lithium ions can move in contact with the positive electrode layer 11 and the negative electrode layer 12. The solid electrolyte layer 13 acts as a separator, allowing lithium ions to pass through while preventing a short circuit between the positive electrode layer 11 and the negative electrode layer 12.
[0072] Here, as a material forming the solid electrolyte layer 13, the same material as the solid electrolyte described above for the positive electrode layer 11 and the negative electrode layer 12 can be applied. Therefore, detailed description of the components is omitted.
[0073] (Positive electrode collector)
[0074] The positive electrode collector 14 can use any material used as the positive electrode collector of this battery without particular limitation. Typically, a metal positive electrode collector having good electrical conductivity is preferred, for example, aluminum, nickel, titanium, stainless steel, copper, and aluminum, nickel, titanium, stainless steel, copper (primer foil) and other metal materials coated with carbon, respectively. Stainless steel (e.g., stainless steel foil) is particularly preferred. The thickness of the positive electrode collector 14 is not particularly limited, but from the perspective of both the capacity density of the battery and the strength of the collector, about 5 μm-50 μm is appropriate, and more preferably about 8 μm-30 μm.
[0075] (Negative electrode current collector)
[0076] The negative electrode current collector 15 can use any material used as the negative electrode current collector of this battery without particular limitation. Typically, a negative electrode current collector made of a metal having good electrical conductivity is preferred, for example, copper (e.g., copper foil) or an alloy mainly composed of copper can be used. The thickness of the negative electrode current collector 15 is not particularly limited, but from the perspective of both the capacity density of the battery and the strength of the current collector, about 5 μm-50 μm is appropriate, and more preferably about 8 μm-30 μm.
[0077] (Combination of positive electrode layer and negative electrode layer)
[0078] Furthermore, the present embodiment is characterized in that the positive electrode layer 11 and the negative electrode layer 12 described above are combined and configured in a predetermined relationship.
[0079] First, the theoretical expansion rate of the active material in the positive electrode layer 11 and the negative electrode layer 12 , the expansion rate of the electrode material containing the active material, and the actual expansion rate of the electrode layer formed using the electrode material are described.
[0080] As described above, expansion and contraction are caused by volume changes of the positive electrode active material and the negative electrode active material during charge and discharge, and are determined by the types and amounts of the positive electrode active material and the negative electrode active material contained and the thickness of the electrode layer.
[0081] <Theoretical expansion ratio of active material>
[0082] The theoretical expansion rate of the active material is specific to its type. For example, some positive electrode active materials and negative electrode active materials are shown in Table 1. In addition, in this specification, the theoretical expansion rate (volume expansion rate) when the volume change of Li metal at 25°C is 100% is expressed.
[0083] [Table 1]
[0084]
[0085] 〈Expansion rate of electrode layer〉
[0086] Furthermore, the expansion rate of the positive electrode layer 11 and the negative electrode layer 12 is calculated by the content ratio of the positive electrode active material contained in the positive electrode layer 11. Similarly, the expansion rate of the negative electrode layer 12 is calculated by the content ratio of the negative electrode active material contained in the negative electrode layer 12. That is, the expansion rate of the electrode layer described here can also be referred to as the expansion rate of the material (composition) forming the electrode layer.
[0087] Among the materials forming the electrode layers used here, the material that contributes to expansion and contraction is the active material. Therefore, the expansion rate of the electrode layer can be calculated based on the content of the active material in the positive electrode layer 11 and the negative electrode layer 12. In addition, the expansion rate of the electrode layer can also be adjusted by adjusting its content.
[0088] 〈Actual expansion ratio of electrode layer〉
[0089] And, based on the expansion rate of the positive electrode layer 11 and the expansion rate of the negative electrode layer 12 calculated as described above, the positive electrode layer 11 and the negative electrode layer 12 of the thickness actually used for the all-solid-state battery 10 are formed. Taking into account the thickness used, the actual expansion ratio of the positive electrode layer 11 and the negative electrode layer 12 is calculated. The actual expansion ratio is calculated as follows using the thickness of the positive electrode layer 11 and the negative electrode layer 12 as a ratio (thickness ratio).
[0090] The actual expansion ratio of the positive electrode layer 11 is calculated by the following formula (1) using the expansion ratio of the positive electrode layer 11 and the thickness ratio of the positive electrode layer 11, and the actual expansion ratio of the negative electrode layer 12 is calculated by the following formula (2) using the expansion ratio of the negative electrode layer 12 and the thickness ratio of the negative electrode layer 12. In addition, the actual expansion ratio is calculated based on the expansion ratio when charging and discharging are started when the surface temperature and the internal temperature of the all-solid-state battery 10 are at 25°C, under the condition that sufficient time has passed to make the surface temperature and the internal temperature of the all-solid-state battery 10 the same temperature.
[0091] Actual expansion ratio of positive electrode layer (Ep) = expansion ratio of positive electrode layer × thickness ratio of positive electrode layer (1) Actual expansion ratio of negative electrode layer (En) = expansion ratio of negative electrode layer × thickness ratio of negative electrode layer (2)
[0092] <Combination of electrode layers>
[0093] Furthermore, in the present embodiment, based on the actual expansion ratio (Ep) of the positive electrode layer and the actual expansion ratio (En) of the negative electrode layer thus obtained, the positive electrode layer 11 and the negative electrode layer 12 are formed so that the absolute value of their difference [(Ep)-(En)] is 10% or less, thereby forming an all-solid battery 10. In order to form such a relationship, the material of the electrode layer can be adjusted, and the thickness of the electrode actually used can be adjusted. Since the material may affect the battery capacity or charge and discharge characteristics, it is realistic to adjust by the electrode thickness.
[0094] The absolute value of the difference in actual expansion ratio [(Ep) - (En)] is preferably as small as possible, and is preferably 5% or less, more preferably 3% or less, further preferably 1% or less, and particularly preferably 0.5% or less.
[0095] More specifically, the electrode materials and electrode layers are formed as shown in Table 2. The combinations described in Table 2 are merely examples and are not intended to be limiting.
[0096] [Table 2]
[0097]
[0098] Table 2 shows that as a conventional example, an active material that is charged and discharged by an insertion reaction is used as an electrode material. Therefore, the theoretical expansion coefficient of such an active material is relatively small as shown in Table 1, and the above-mentioned problems listed as conventional problems are unlikely to occur.
[0099] In contrast, in the electrodes A to C, active materials that are charged and discharged by conversion reactions are used as electrode materials. As shown in Table 1, the theoretical expansion coefficient of such active materials is relatively large, and the expansion coefficient of the electrode layer formed using these materials is also likely to become large. As shown in Table 2 above, when the expansion coefficient of the electrode layer exceeds 10%, in particular, the problems described in the above-mentioned previous topics are likely to occur. Therefore, by adopting the structure shown in this embodiment, the decrease in cycle characteristics can be effectively suppressed.
[0100] And, refer to Figure 2A and Figure 2B The principle that the cycle characteristics can be suppressed from being degraded by satisfying such a relationship is explained below. Figure 3 same, Figure 2A and Figure 2B This is a schematic diagram for explaining the behavior during charge and discharge. Figure 2A This is an example of initial charging. Figure 2B This is an example of the initial discharge.
[0101] First, an all-solid-state battery 10 is prepared, wherein, as described in the present embodiment, a positive electrode layer 11, a negative electrode layer 12, a solid electrolyte layer 13 formed between the positive electrode layer 11 and the negative electrode layer 12, and a positive electrode collector 14 and a negative electrode collector 15 ( Figure 2A (a)).
[0102] Next, the all-solid-state battery 10 is initially charged. In the present embodiment, since the active material with a large theoretical expansion rate is contained, during the initial charge, the negative electrode layer 12 expands greatly in the stacking direction, while the positive electrode layer 11 contracts greatly in the stacking direction. In this case, in the present embodiment, as described above, the positive electrode layer 11 and the negative electrode layer 12 are formed so that their actual expansion ratios are close to each other. Therefore, the changes (expansion amount and contraction amount) of the positive electrode layer 11 and the negative electrode layer 12 are close, and thus Figure 3Unlike the all-solid-state battery 50 described in the embodiment, the solid electrolyte layer 13 is not compressed ( Figure 2A (b)).
[0103] When the charge is completed and the discharge is performed, the positive electrode layer 11 expands and the negative electrode layer 12 contracts. In this case, since the amount of change (expansion amount and contraction amount) of the positive electrode layer 11 and the negative electrode layer 12 is close, the solid electrolyte layer 13 is not affected by the force of separation of the negative electrode layer 12 from the contact surface ( Figure 2A (c)).
[0104] In the case of initial discharge, as described above, first, a fully solid battery 10 is prepared, which is stacked with a positive electrode layer 11, a negative electrode layer 12, a solid electrolyte layer 13 formed between the positive electrode layer 11 and the negative electrode layer 12, and also has a positive electrode collector 14 and a negative electrode collector 15 ( Figure 2B (a)).
[0105] Next, the all-solid-state battery 10 is initially discharged. In the present embodiment, since the active material having a large theoretical expansion rate is contained, during the initial discharge, the positive electrode layer 11 expands greatly in the stacking direction, while the negative electrode layer 12 contracts greatly in the stacking direction. In this case, in the present embodiment, as described above, the positive electrode layer 11 and the negative electrode layer 12 are formed so that their actual expansion ratios are close to each other. Therefore, the changes (expansion amount and contraction amount) of the positive electrode layer 11 and the negative electrode layer 12 are close, and thus Figure 3 Unlike the all-solid-state battery 50 described in the embodiment, the solid electrolyte layer 13 is not compressed ( Figure 2B (b)).
[0106] When charging is performed after discharge is completed, the negative electrode layer 12 expands and the positive electrode layer 11 contracts. In this case, since the amount of change (expansion amount and contraction amount) of the positive electrode layer 11 and the negative electrode layer 12 is close, the solid electrolyte layer 13 is not affected by the force of separation of the negative electrode layer 12 from the contact surface ( Figure 2B (c)).
[0107] Therefore, in the all-solid battery 10 of this embodiment, when charging and discharging, no large stress is generated at any interface between the positive electrode layer 11 and the solid electrolyte layer 13, and the negative electrode layer 12 and the solid electrolyte layer 13, and the situation where their contact area decreases and the interface resistance increases can be suppressed. Thus, even through repeated charging and discharging, significant degradation of the cycle characteristics can be avoided, and an all-solid battery with good characteristics can be made.
[0108] [Method for preparing all-solid-state battery]
[0109] The preparation method of the all-solid battery of the present embodiment is characterized in that the all-solid battery of the structure described above is prepared, and the preparation method can be operated in the same manner as the conventionally known preparation method. That is, the all-solid battery in the present embodiment can be prepared by forming a positive electrode layer 11, a negative electrode layer 12 and a solid electrolyte layer 13 respectively, and stacking them to form a stacked electrode body.
[0110] For example, similar to conventional batteries of this type, the positive electrode layer 11, the negative electrode layer 12, and the solid electrolyte layer 13 can be formed by preparing a paste (slurry) composition containing the above-mentioned various components, applying the paste (slurry) composition on the positive electrode collector 14 or the negative electrode collector 15, drying it, and pressing it at an appropriate pressure (for example, about 5MPa-300MPa).
[0111] Then, the positive electrode layer 11 and the negative electrode layer 12 are stacked with the solid electrolyte layer 13 interposed therebetween to form a stacked electrode body, and then, the stacked electrode body is pressed at a predetermined pressure (e.g., 2-4 tons / cm 2 ) The stacked electrode body is pressurized to improve the mechanical strength of the stacked electrode body and the conductivity (in other words, the ion conduction path) in each layer. In addition, the positive terminal and negative terminal (not shown) for external connection are connected to the positive electrode collector 14 and the negative electrode collector 15, respectively.
[0112] At this time, the actual expansion ratio (Ep) of the positive electrode layer and the actual expansion ratio (En) of the negative electrode layer are combined so that the absolute value of the difference [(Ep) - (En)] between them is within 10%.
[0113] At this time, the obtained all-solid battery is subjected to an initial charge treatment and then an initial discharge treatment, and further subjected to an appropriate aging treatment as desired, thereby preparing a usable all-solid battery (in this embodiment, an all-solid lithium ion secondary battery) 10.
[0114] The all-solid-state battery 10 of the present embodiment is similar to the previous batteries of this type, and is housed in an outer casing (not shown) having a shape corresponding to the shape of the laminate obtained by the above-mentioned stacking. There is no particular restriction on the material constituting the outer casing. For example, from the viewpoints of high physical strength, heat dissipation, etc., a metal (e.g., aluminum) outer casing can be preferably used. Alternatively, from the perspective of loading capacity or the overall light weight of the battery module, it can also be composed of a laminated film. As a preferred example in this case, a laminated film having a three-layer structure in which a metal layer is arranged between two synthetic resin layers can be cited.
[0115] Furthermore, when the all-solid-state battery disclosed herein is used as a high-output power source for driving a vehicle, a plurality of all-solid-state batteries may be connected to each other to form a battery module.
[0116] As mentioned above, although this invention was demonstrated concretely through embodiment, this invention should not be construed as being limited to these embodiment, Of course, various changes can be made in the range which does not deviate from the summary.
[0117] Explanation of symbols
[0118] 10,50 All-solid-state battery
[0119] 11,51 positive electrode layer
[0120] 12,52 negative electrode layer
[0121] 13,53 Solid electrolyte layer
[0122] 14,54 positive electrode collector
[0123] 15,55 negative electrode collector
Claims
1. An all-solid-state battery, which is an all-solid-state battery that is charged and discharged by a conversion reaction, comprising a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer and containing a solid electrolyte, in, The absolute value of the difference [(Ep)-(En)] between the actual expansion ratio (Ep) of the positive electrode layer calculated by the following formula (1) and the actual expansion ratio (En) of the negative electrode layer calculated by the following formula (2) is 10% or less, The actual expansion ratio of the positive electrode layer (Ep) = the expansion rate of the positive electrode layer × the thickness ratio of the positive electrode layer (1) The actual expansion ratio of the negative electrode layer (En) = the expansion rate of the negative electrode layer × the thickness ratio of the negative electrode layer (2).
2. The all-solid-state battery according to claim 1, wherein: The expansion rate of the positive electrode layer and / or the negative electrode layer is greater than 10%.
3. The all-solid-state battery according to claim 1, wherein: The positive electrode active material is formed of a material selected from CuCl 2 , FeF 2 and S, and the negative electrode active material is formed of a material selected from Si, Li, Mg and Al.
4. The all-solid-state battery according to claim 1, wherein: The positive electrode layer contains a positive electrode active material, a solid electrolyte, a conductive additive and a binder. The content ratio based on mass is positive electrode active material: conductive auxiliary agent: When binder:solid electrolyte=x:y:z:v is expressed, the content ratio (mass %) thereof is in the range of 50≤x≤92.5, 2.5≤y≤45, 2.5≤z≤45, and 2.5≤v≤45.
5. The all-solid-state battery according to claim 1, wherein: The negative electrode layer contains a negative electrode active material, a solid electrolyte, a conductive additive and a binder. The content ratio based on mass is positive electrode active material: conductive auxiliary agent: When binder:solid electrolyte=x:y:z:v is expressed, the content ratio (mass %) thereof is in the range of 50≤x≤92.5, 2.5≤y≤45, 2.5≤z≤45, and 2.5≤v≤45.
6. The all-solid-state battery according to claim 1, wherein: The absolute value of the difference [(Ep) - (En)] is 5% or less.
7. The all-solid-state battery according to claim 1, wherein: The absolute value of the difference [(Ep) - (En)] is 1% or less.
8. A method for preparing an all-solid-state battery, which is a method for preparing an all-solid-state battery that is charged and discharged by a conversion reaction, the method comprising: A step of preparing a positive electrode layer including a positive electrode active material, a negative electrode layer including a negative electrode active material, and a solid electrolyte layer including a solid electrolyte; and a step of stacking the positive electrode layer, the negative electrode layer and the solid electrolyte layer so as to be arranged between the positive electrode layer and the negative electrode layer, and pressing in a stacking direction, The absolute value of the difference between the actual expansion ratio (Ep) of the positive electrode layer calculated by the following formula (1) and the actual expansion ratio (En) of the negative electrode layer calculated by the following formula (2) is less than 10%. The actual expansion ratio of the positive electrode layer (Ep) = the expansion rate of the positive electrode layer × the thickness ratio of the positive electrode layer (1) The actual expansion ratio of the negative electrode layer (En) = the expansion rate of the negative electrode layer × the thickness ratio of the negative electrode layer (2).
Citation Information
Patent Citations
Negative electrode for all-solid battery
JP2017054720A